Los nuevos rostros de la música andina a través de los instrumentos musicales - Robles Mendoza, Román (2007)
Music is in everywhere, an important component of the culture of the towns, to give solemnity to the established rituals and to provide joy to its ceremonies and custom celebrations of all type. In this work we make a fast revision of the traditional use of the musical instruments in the Andes of the Peru and the process of changes in the conformation of the musical organizations happened from the introduction of European instruments. The general perspective of the treatment of the musical instruments leans in the empirical information of the old Cajatambo, region located to the north of Lima and the south of Ancash.